221k views
2 votes
Simplify to create an equivalent expression. 6(7−3y)+6(y+1)

User Rvy Pandey
by
5.7k points

2 Answers

5 votes

Answer:

48 = 12y

Explanation:

First, we simplify

6 * 7 = 42

6 * 3y = 18y

6 * y = 6y

6 * 1 = 6

Then, rewrite the expression

42 - 18y + 6y + 6

Now, rearrange the expression

42 + 6 - 18y + 6y

Then, simplify

48 - 12y

Hope this helps!

User Havox
by
5.1k points
3 votes

Answer:

48 - 12 y

Explanation:

6 (7 - 3 y) + 6 (y + 1)

Use distributive property to get rid of the parentheses:

42 - 18 y + 6 y + 6

now combine like terms:

(42 + 6 ) + (- 18 y + 6 y) = 48 - 12 y

User SmileyChris
by
5.5k points